El hábitat de los animales y las plantas - Tesen Calderon, Valentin (2018)
Our work as teachers constantly leads us to share with our students experiences, anecdotes, concerns that allow them to learn from their context and their interests and needs, in contact with the elements, beings and objects that constitute it. The first chapter includes the application of strategies that will be developed in each of the pedagogical processes, through the combination of capacities to recognize the characteristics of the habitat of the animals and plants of the region. The second chapter corresponds to the theoretical foundation of the area of science and technology and its thematic contents. The following chapter considers the pedagogical support on which the disciplinary content of the session to be treated is based from a scientific inquiry and literacy approach.